A Decade of Global and Local Brand Research: A Systematic Literature Review by Using SLR PRISMA - Fitriana, Ana (International Journal of Economic, Finance and Business Statistics, 2024)
This systematic literature review aims to synthesize the evolving research on global and local brand dynamics over the past decade using the PRISMA methodology. It examines the shift from a simplistic global-local dichotomy to a more nuanced understanding of how these brand types interact with consumer identities, digital platforms, sustainability, and global crises. The study explores the emergence of "glocal" branding strategies and the recognition of simultaneous global and local brand perceptions as significant theoretical advancements. However, it highlights the growing complexity introduced by digital transformation, corporate social responsibility, and the COVID-19 pandemic, necessitating more integrative frameworks. The review identifies persistent gaps and opportunities for future research, including investigating the impact of digital platforms, sustainability initiatives, and post-pandemic consumer behavior shifts on global-local brand dynamics. By consolidating diverse research streams, the study proposes an integrative framework that accounts for the intricate interplay of cultural, digital, and global factors shaping brand perceptions and preferences. Overall, the findings extend existing knowledge and offer valuable insights for academics and practitioners navigating the evolving landscape of global and local branding.